2018
DOI: 10.5964/ejop.v14i3.1490
|View full text |Cite
|
Sign up to set email alerts
|

From organizational justice perceptions to turnover intentions: The mediating effects of burnout and job satisfaction

Abstract: Turnover intentions (TI) stand as an insidious problem that impacts on the functioning of organizations and the well-being of their members. Currently, there is a growing interest in identifying the explanatory mechanisms of TI, in order to strengthen and retain valued employees for organizations. In line with this trend, the aim of the present study was to test an integrative serial multiple mediation model that examined the possible mediating role of burnout and job satisfaction in the relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 37 publications
(99 reference statements)
3
28
1
Order By: Relevance
“…This result is a similar line with Vaamonde et al, [45] who found that the highest mean score of participant perception was interactional justice while the lowest mean score was distributive justice. On the contradicting with the present findings, the results of Tourani et al, [46] found that the participants' perception of the highest mean score was for the distributive justice while the lowest mean score was for interactional justice.…”
Section: Results Regarding the Three Dimensions Of Organizationalsupporting
confidence: 91%
“…This result is a similar line with Vaamonde et al, [45] who found that the highest mean score of participant perception was interactional justice while the lowest mean score was distributive justice. On the contradicting with the present findings, the results of Tourani et al, [46] found that the participants' perception of the highest mean score was for the distributive justice while the lowest mean score was for interactional justice.…”
Section: Results Regarding the Three Dimensions Of Organizationalsupporting
confidence: 91%
“…Again, Harris et al (2018) acknowledged that perception of client-focused justice predicts employee turnover intention. Moreover, Vaamonde et al (2018) found the dimensions of justice (i.e., distributive, procedural and interpersonal justice) have negative indirect effects on turnover intentions through burnout and job satisfaction. These results indicate that distributive, procedural and interpersonal justice perceptions relate to lower levels of burnout, which in turn promote greater job satisfaction and lower turnover intentions among employees.…”
Section: Introductionmentioning
confidence: 97%
“…One of the triggering elements of this emotion can be expressed as the perceptions of justice of the employees (Elovainio, Kivimäki, & Vahtera, 2002;Chênevert et al, 2013). In the studies aimed at determining the relationship between organizational justice dimensions and emotional burnout in literacy, it is observed that operational, distributive and interaction justice negatively affects the depletion (Vaamonde, Omar & Salessi, 2018;Safari, Tamizifar & Jannati, 2012;Lambert et al, 2010;Chênevert et al, 2013). In this study, it is concluded that the operational, distribution and interaction justice affects the emotional exhaustion and the distribution justice also affects desensitization negatively.…”
Section: Discussionmentioning
confidence: 99%